Childhood Non Communicable Diseases (NCDs) in Two Tertiary Hospitals in South-South Nigeria - , Nsirimobu I. Paul, Chika O. Duru (Archives of Current Research International, 2020)
Background: As in adults, there is a high burden of non-communicable diseases (NCDs) in children and this is often associated with a high mortality rate, however, little emphasis is being paid to NCDs in children. Objective: The objective of this study was to determine the burden, pattern and mortality associated with NCD among children admitted into the Paediatric wards of two tertiary centres in South-South Nigeria. Methods: This was a retrospective study carried out in two tertiary hospitals in South-South Nigeria. Medical/admission records of all patients with Non communicable diseases (NCDs) were retrieved. Information obtained included patient's age, sex, date of admission, final diagnosis, date of discharge and hospital outcome. Total number of admissions and deaths within the study period were also obtained. The diagnoses were classified according to pathologic and systematic derangement. Obtained data were analysed using Statistical Package for Social Sciences (SPSS) version 20.0 and presented in frequency tables and charts while chi square and Fischers exact test were used to compare categorical variables. Statistical significance was set at P < 0.05. Results: A total of 4,167 patients were hospitalized over the study period, out of which 897 had NCDs giving a prevalence rate of 21.52%. Of the NCDs, 570 (63.55%) were males while 327 (36.45%) were females giving a male female ratio of 1.74:1. Haematology, Oncology (Cancers), Nephrology, Neurology and Cardiology disorders were the five common NCDs and constituted about three quatre (74.47%) of all NCDs. Among the five common NCDs, haematology, oncology and nephrology disorders were commoner in the older children while cardiac, and neurologic disorders were more prevalent in younger children. This distribution was not statistically significant (X2 = 1.67, p = 0.9800). Sickle cell anaemia (SCA) was the prevalent Haematological disease constituting 176 (95.1%) of all haematological cases. Acute lymphoblastic leukaemia, Nephrotic syndrome, Seizure disorder and Ventricular septal defect were the prevalent cancers, Nephrology, neurology and cardiac disorders and constituted 50 (27.6%), 39 (28.7%), 33 (40.74%), 21 (25.0), of the diseases respectively. A total of 112 deaths occurred in the Paediatric wards over the study period, 35 (31.25%) of these deaths were caused by NCDs and patients with Cancers constituted 60% (21/35) of all deaths. More deaths occurred among the adolescents; however, this was not statistically significant. (chi square = 21.99, p=0.1081). Conclusion: There is a high burden and high mortality of NCDs in children in our environment. The common pattern of NCDs were Haematology, Oncology (Cancers), Nephrology, Neurology and cardiology diseases. Improved health education, early cancer screening and availability of cancer and prenatal diagnosis of SCA screening tools, premarital genotype counselling and screening and legislation to support families with NCDs is advocated.